2022
DOI: 10.3390/jcm11237043
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Eye Movements and Asthenopia: A Prospective Observational Study

Abstract: Purpose: To analyze the correlation between eye movements and asthenopia so as to explore the possibility of using eye-tracking techniques for objective assessment of asthenopia. Methods: This prospective observational study used the computer visual syndrome questionnaire to assess the severity of asthenopia in 93 enrolled college students (age 20–30) who complained about asthenopia. Binocular accommodation and eye movements during the reading task were also examined. The correlations between questionnaire sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Those studies that previously compared CVS-Q data with full optometric findings reported unconvincing results. [51][52][53] These studies indicated that the CVS-Q items are multifactorial and seem to be more related to dry eye syndrome than binocular/accommodative anomalies or internal symptoms of asthenopia (see Figure 2). It should be noted that the CVS-Q was developed to assess visual symptoms related to computer use, but seems to be too specific to assess asthenopia, which was evaluated as accommodative fatigue.…”
Section: Subjective Assessment Of Visual Fatigue and Optometric Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies that previously compared CVS-Q data with full optometric findings reported unconvincing results. [51][52][53] These studies indicated that the CVS-Q items are multifactorial and seem to be more related to dry eye syndrome than binocular/accommodative anomalies or internal symptoms of asthenopia (see Figure 2). It should be noted that the CVS-Q was developed to assess visual symptoms related to computer use, but seems to be too specific to assess asthenopia, which was evaluated as accommodative fatigue.…”
Section: Subjective Assessment Of Visual Fatigue and Optometric Resultsmentioning
confidence: 99%
“…To the best of our knowledge, no study has compared objective laboratory metrics of accommodation between individuals classified as either non‐asthenopic or asthenopic. Those studies that previously compared CVS‐Q data with full optometric findings reported unconvincing results 51‐53 . These studies indicated that the CVS‐Q items are multifactorial and seem to be more related to dry eye syndrome than binocular/accommodative anomalies or internal symptoms of asthenopia (see Figure 2).…”
Section: Discussionmentioning
confidence: 99%